Long-term outcomes of LASIK for myopia: Poster Presentation - Observational Study - General practitioner - Tania; Mattarungan, Monica (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Myopia is a major healthcare burden worldwide. Refractive surgery is used to correct refractive error for patients who wanted less reliance on glasses and contact lenses. LASIK is one of the most commonly used procedures for correction of myopia. This study aims to evaluate the long-term outcomes of LASIK procedure for myopia. Methods : A literature search was conducted for the years of 2017 to 2013 from PubMed with the search term "LASIK" AND "myopia" AND ("efficacy" OR "long-term outcomes"). All abstracts were reviewed and evaluated, and articles relevant to the topic was reviewed for this study. Results : Out of 71 articles from search results, 7 articles were selected for review. At the last follow up from 3-12 years, uncorrected distance visual acuity (UDVA) of -0.03 – 0.39 logMAR was achieved. Around 64% - 90% patients achieved UDVA of 20/20 or better. Myopic progression was found with the mean of 0.63 – 0.97 D. The efficacy index and safety index was at 0.67 - 1.01 MR and 1.02 - 1.09 respectively at the end of follow up. Conclusion : The data showed that LASIK had an excellent long-term safety and efficacy for treatment of myopia, although small percentage of patients experienced mild myopic progression.